Re-exposure in cone beam CT of the dentomaxillofacial region: a retrospective study - Habibi, Yasamin; Habibi, Edriss; Al-Nawas, Bilal (Dentomaxillofacial radiology, 2019)
Objectives: Cone beam CT (CBCT) often uses a smaller field of view compared to conventional CT scans. This might lead to a wrong field of view with the need for secondary exposure (“retakes”). The purpose of this retrospective study was to assess the frequency of re-exposures in CBCT and to identify whether the parameters age, gender, and field of view have an influence on the re-exposure of the patient. Additionally, the causes of re-exposures were determined and categorized. Methods: In a retrospective cohort study CBCT images of 4986 patients from the patient database from the Department of Oral Radiology, University Medical Center of the Johannes Gutenberg University, Mainz, Germany were included and the rate of re-exposures was counted. Patients were stratified into those who received a scan with the small field-of-view CBCT or the large field-of-view CBCT. The effect of patient-related parameters as age and gender was implicated. As a further device-specific parameter, the statistical analysis included whether the selection of the field of view due to the device type had a significant influence on the occurrence of re-exposures. Furthermore, the rescans were analyzed with regard to their causes. Results: In total, CBCT images of 82 (1.6%) patients had to be repeated. Looking at the two different devices, in 42 (1.3%) patients that received a scan with the large field-of-view CBCT and in 40 (2.3%) patients that received a scan with the small field-of-view CBCT respectively needed a retake. There was no statistically significant correlation between age and gender to retakes. For the small field-of-view-size significantly more retakes were observed than for the large one. With 46% motion artifacts were the most frequent causes for a re-exposure of the patient. Conclusions: Gender and age did not have an impact on the occurrence of re-exposures. Patients who received a scan with the small field-of-view CBCT were significantly more often rescanned than those with the large field-of-view CBCT.
Gesehen am 24.06.2019